(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
In developing countries’ legislation, the difference between investment banking and commercial banking are ignored, and so are the consequences that the combination of both banking activities might have. The mix of these activities, apart from being a huge challenge for regulatory authorities, constitutes a business decision that could boost corruption from the banking sector, by offering to consumers unusual products, endorsed by financial instruments that are, in turn, captured by investor clients of the same bank. With that in mind, it is evident that any conflict of interests or unlawful act made by the bank sector will have a negative impact on consumers. Consequentially, it is important to raise the following question: ¿is it prudent to combine investment and commercial banking in Paraguay?